INTEGRATION OF HOTS-BASED QUIZIZZ APPLICATION TO IMPROVE MATHEMATICAL LITERACY ABILITIES OF VOCATIONAL SCHOOL STUDENTS - Nur Tri Julia; Weni Widya Asriati; Fikri Fikri (Program Studi Pendidikan Matematika, Universitas Bina Bangsa Getsempena, 2025)
This study was motivated by the need for contextual, interactive assessments aligned with the characteristics of the Merdeka Curriculum in developing students’ mathematical literacy skills. The purpose of this research was to develop a Merdeka Belajar assessment based on ethnomathematics and Higher Order Thinking Skills (HOTS) integrated with the digital application Quizizz to enhance students’ mathematical literacy. The study was conducted at Dharma Pancasila Private Vocational School (SMK Swasta Dharma Pancasila) in Medan during the odd semester of the 2025/2026 academic year, employing a Research and Development (R&D) approach using a modified Dick & Carrey model through several stages: needs analysis, design, development, validation, limited trial, and field testing. The research subjects were ninth-grade students selected through total sampling. The research instruments included expert validation sheets, mathematical literacy tests, questionnaires, interviews, and observations. The expert validation results indicated that the developed assessment was categorized as very valid, with an average score of 4.52. The limited trial results showed that 93% of students stated that the questions were easy to understand, and 100% found the Quizizz application easy to use. The effectiveness test demonstrated an increase in the average score from 62.3 to 84.1 with an N-Gain value of 0.58 (moderate–high category). The independent t-test result showed a significance value of p = 0.003 < 0.05, indicating a significant difference between pretest and posttest results. The study concluded that the assessment based on ethnomathematics, HOTS, and Quizizz was proven to be valid, practical, effective, and well-received by both students and teachers. The implication of this research is that this assessment model can serve as an innovative alternative to strengthen mathematical literacy, integrate local cultural values, and support the digital and sustainable implementation of the Merdeka Curriculum.